Reaktualisasi Hukum Islam dan Fikih Sosial: Analisis Pemikiran Munawir Sjadzali dan K.H. Sahal Mahfudz - Prihastama, Fauzi; Ahmad, Mukhsin (TAQNIN: Jurnal Syariah dan Hukum, 2024)
This study explains the Reactualization of Islamic Law and Social Jurisprudence, according the thoughts of Munawir Sjadzali and KH. Sahal Mahfudz. This study tries to present the thoughts of Indonesian Islamic legal figures in providing a new paradigm in understanding contemporary Islam and adaptable to the times and social developments of today's society. Therefore, this research is important to find out how these two figures think and their relevance to today's life which has developed both in terms of technology, culture and thought. This research aims to present the Islamic legal thinking of two reform figures, namely Munawir Sjadzali and KH. Sahal Mahfudz who provides a new style in the interpretation of Islamic law that is more adaptable to current developments, such as thinking about the Reactualization of Islamic Law and Social Jurisprudence in the context of the formation of Social Jurisprudence that is suitable for application today. This research is qualitative research with a library approach. The results of this research show that the thoughts of these two figures have contributed to understanding Islam which can follow and face the era of globalization and contemporary developments.